Gut microbiota and urine metabolomics based exploration of Coreopsis tinctoria Nutt. tea on type 2 diabetic mellitus - Jing Liu; Yuqing Pang; Hongxia Yang; Dongna Huo; Xiuxue Liu; Xiaopeng Chen (Arabian Journal of Chemistry, 2023)
Scented tea, as an integral part of tea culture for several centuries, is important to prevent chronic metabolic diseases. Coreopsis tinctoria Nutt. (CT) tea is often used to prevent and treat diabetes, but the mechanism of action needs further study. Liquid chromatography-mass spectrometry was used to analyze 23 chemical components of CT extracts, and a “compounds-target-healthy function” network was constructed while the pathway enrichment analysis was carried out. Eleven CT compounds, including flavanomarein, luteolin, isookanin, marein, 7,3′,5′-trihydroxy-flavanone, okanin, caffeic acid, cynaroside, acetylcoreopsin, quercetin-7-O-β-D-glucoside, protocatechuic acid, were obtained through network pharmacology screening. The corresponding targets SRC, TP53, HSP90AA1, STAT3, MAPK1, PIK3R1, AKT1 and PIK3CA were associated with anti-glycemic effects. The rat model of type 2 diabetic mellitus (T2DM) was induced by a high-fat diet combined with low-dose streptozotocin injection and biochemical indexes (blood glucose, serum total cholesterol, and triglyceride) were determined. The low-dose water extract of CT can significantly regulate the total cholesterol level of diabetic rats (p < 0.01). 16S rDNA sequencing showed that CT could reverse the imbalance of intestinal flora, especially Lactobacillus, Prevotella, Succinivibrio, unidentified_Ruminococcaceae, and Treponema. Urine metabolomics observed 31 differential metabolites, mainly related to Glycerophospholipid metabolism. The correlation study showed that CT could treat T2DM by modulating the interaction of gut microbiota composition, changes in key bacterial genera, and the levels of endogenous metabolites to act on carbohydrate metabolism, amino acid metabolism, and lipid metabolism pathways. Therefore, CT water extract can effectively alleviate the changes of T2DM may be related to the combined changes of intestinal flora and metabolic characteristics.